Dalihan NATOLU Customary Law as an Alternative Solution to Preventing and Eradicating Narcotics Crimes - Oskar Refelino Tambunan; T Riza Zarzani; Henry Aspan (PT. Sinergi Legal Publisher, 2024)
Drug crimes are a serious threat in Indonesia, and the positive legal approach has not been effective enough in overcoming it. Dalihan Na Tolu customary law, which applies in the Batak Toba community, offers an alternative community-based solution through three main pillars: Mora, Kahanggi, and Anak Boru. These principles, which emphasize respect, responsibility, and togetherness, can support drug prevention through social control and character education. This study explores the potential of Dalihan Na Tolu customary law as a holistic approach integrated into the national legal system, helping to ease the burden on formal law enforcement and strengthening community participation. By recognizing this customary law, drug prevention efforts are expected to be more effective, inclusive, and sustainable.